Mobilization and Redistribution of Elements in Laterites of Semail Ophiolite, Oman: A Mass Balance Study - Salah Al Khirbash; Khadija Semhi (Sultan Qaboos University Journal for Science, 2015)
Several samples of laterites were collected from four paleosol profiles, Ibra, East Ibra, Al-Russayl, and Tiwi representing the vertical lithological variation within each profile. The mineralogical and geochemical composition of laterites in every section revealed differences in thickness and redistribution of elements reflecting different conditions of weathering processes. Elemental mass balance was calculated for every profile relative to the parent rock. The results indicated redistribution of elements from the surface to deeper zones with an enrichment of elements in the saprolite and oxide zones. Among the different sections, the profile of East Ibra composite 1 and 2 is characterized by high concentration of all elements compared to the other profiles. Sc/Fe ratio in different zones indicates low values for the profile of Tiwi profile 1, Ibra profile and Al-Russayl composite 2 and 3 profile due to the significant enrichment of Fe in these zones independently of redox conditions. Large fluctuations characterize Th/U ratios and reflect redox condition more reduced in Tiwi area than in East Ibra and Al-Russayl areas.